Tackling income inequality The role of taxes and transfers - Joumard, Isabelle (OECD Publishing, 2012)
Taxes and transfers reduce inequality in disposable income relative to market income. The effect varies, however, across OECD countries. The redistributive impact of taxes and transfers depends on the size, mix and the progressivity of each component. Some countries with a relatively small tax and welfare system (e.g. Australia) achieve the same redistributive impact as countries characterised by much higher taxes and transfers (e.g. Germany) because they rely more on income taxes, which are more progressive than other taxes, and on means-tested cash transfers. This article provides an assessment of the redistributive effect of the main taxes and cash transfers, based on various OECD data sources, a set of policy indicators and a literature review. Using cluster analysis, it also identifies empirically four groups of countries with tax and transfer systems that share broadly similar features